2018
DOI: 10.1177/1553350618781622
|View full text |Cite
|
Sign up to set email alerts
|

Choledochoscopic Examination of a 3-Dimensional Printing Model Using Augmented Reality Techniques: A Preliminary Proof of Concept Study

Abstract: AR techniques can be used to assist navigation in choledochoscopy examinations in bile duct models. Further research is needed to determine its benefits in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…As shown in Table 2 , current 3D printing enables the adjustment and placement of 3D printed models in optimal anatomical positions, facilitating both the placement of surgical instruments and the intuitive real-time navigation of key steps in surgery. It also allows rapid identification and precise positioning of key sites, optimizing the plane of surgical resection, the separation of important vessels and the precise removal of lesions, thereby improving surgical precision and safety and reducing surgical risk[ 29 ]. A number of studies have shown that 3D printing can produce implant shapes that precisely match their anatomical characteristics, ensuring that implant surgery is carried out safely[ 30 , 31 ].…”
Section: Three-dimensinal Visualization Images and Their Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2 , current 3D printing enables the adjustment and placement of 3D printed models in optimal anatomical positions, facilitating both the placement of surgical instruments and the intuitive real-time navigation of key steps in surgery. It also allows rapid identification and precise positioning of key sites, optimizing the plane of surgical resection, the separation of important vessels and the precise removal of lesions, thereby improving surgical precision and safety and reducing surgical risk[ 29 ]. A number of studies have shown that 3D printing can produce implant shapes that precisely match their anatomical characteristics, ensuring that implant surgery is carried out safely[ 30 , 31 ].…”
Section: Three-dimensinal Visualization Images and Their Extensionmentioning
confidence: 99%
“…There is also a transparent display in use that reflects the image in a translucent mirror, allowing the surgeon to view the reconstructed image while also looking directly into the surgical field. It does not require additional video compositing, making it more convenient than conventional video displays and avoids the problem of distortion of the projected image due to changes in the curvature of the object's surface, in addition it does not require special glasses or sensing devices, future research will require improved transparent display methods and more advanced naked eye 3D to provide doctors with a more accurate display of spatial images[ 29 ].…”
Section: Real-time Navigationmentioning
confidence: 99%
“…Symptomatic patients or those with laboratory derangements of obstructive jaundice or liver dysfunction may benefit from endoscopic stones and sludge removal, dilation, and stenting in select cases [53]. For biliary endoscopy, previous work show 3D printed anatomic models being used primarily in training applications [29,30]. 3D printing has been used in the development of novel biliary stents [54].…”
Section: Hepatobiliarymentioning
confidence: 99%
“…They can enlighten the patients about their condition, and contribute to the facilitation of a better understanding and patient-physician collaboration. Tang et al[49] proposes the use of 3D printed models when training in AR-assisted endoscopy. Although the setting and equipment were described thoroughly, there were no quantitative variables in the study that could measure the benefit of this method.…”
Section: Current Status and Challenges Of 3d Printing In Hepatic Surgerymentioning
confidence: 99%